Burnout, Resilience and Job Satisfaction in Acute Care Nurse Practitioners - Lori Harwood, Jacqueline Crandall and Anthony LeFuentes (Nursing Leadership, 2024)
Emerging from a pandemic only to enter a nursing shortage has placed a strain on the health human resources of the healthcare system. Little attention has been given to nurse practitioners' (NPs’) burnout, resilience and job satisfaction. In this quantitative cross-sectional study using the Maslach Burnout Inventory, Misener NP Job Satisfaction Scale and the Connor-Davidson Resilience Scale, an alarming level (80.9%) of NPs reported high to moderate levels of burnout (emotional exhaustion), on average, minimal job satisfaction and high levels of resilience. Hospital leaders play a major role in NP role optimization, NP recruitment and retention and quality of work–life issues.
Keywords: nurse practitioner, burnout, job satisfaction, resilience, onboarding, novice NPs, NP role